SINERGISITAS SATUAN POLISI PAMONG PRAJA, KEPOLISIAN DAN PEMERINTAH DAERAH DALAM MENEGAKKAN KEAMANAN DAN KETERTIBAN MASYARAKAT (Institut Pemerintahan Dalam Negeri, 2020)
Satpol PP as a regional apparatus has a very strategic role in strengthening regional autonomy and public services in the regions. To guarantee the implementation of Satpol PP’s duties in the enforcement of Regional Regulations and Regional Regulation, the implementation of public order and peace and community protection needs to be improved, both in terms of institutional and human resources. In addition, the existence of Satpol PP in the administration of regional government is expected to help ensure legal certainty and facilitate the development process in the regions. This research method uses a type of normative and descriptive juridical research that aims to describe the relationship of the main tasks and authorities and obligations between the Civil Service Police Unit and the Regional Government Police in upholding order in society. The purpose of this research is to ϔind out and describe the synergy between Satpol PP, the Police and Local Government in carrying out their duties or obligations to maintain public security and order in accordance with the main task of Satpol PP No. 16 of 2018, the police as stipulated in Article 13 of Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia and the obligations of the Regional Government based on Article 43 of Law No. No. 23 of 2014 concerning Regional Government. Keywords: Satpol PP, Police, Local Government, Community Order